DAMPAK COVID-19 TERHADAP PERUBAHAN HARGA SAHAM DAN VOLUME TRANSAKSI SAHAM SYARIAH (STUDI KASUS PADA PT. UNILEVER, TBK) - Dian Nilam Sari; Yolanda Wahyu Lestari (J-EBI: Jurnal Ekonomi Bisnis Islam, 2022)
COVID-19 is the latest virus that appeared around December 2019 in Wuhan, China. The virus is spreading rapidly in various parts of the country, including Indonesia. This virus that spreads in Indonesia breaks the myth of "immune" to covid-19. The virus had a negative impact on health. In addition, all sectors are affected as much as the investment sector. COVID-19 cases in Indonesia was announced on March 2, 2020. This study aims at finding out whether there is a significant difference in stock prices and the volume of stock transactions before and after the announcement of COVID-19 (case study of PT Unilever, Tbk). This study uses quantitative research and the data collection methods are using secondary data. The research data was taken before and after 31 days COVID-19 announcement. The researcher uses statistical test using Paired Sample T-Test stated, by using a statistical version 23. From the results of data processing, it shows that there is a significant difference in stock price of PT Unilever, Tbk before and after the announcement of COVID-19. This is indicated by a significance value of 0.00 0.05. Which is the stock price has decreased after the COVID-19 announcement than before the COVID-19 announcement. Meanwhile, the volume of stock transactions before and after the Covid-19 announcement also showed a significant difference. Which is the significance value is 0.00 0.05. Before the Covid-19 announcement, the volume of stock transactions had increased meanwhile had decreased after the Covid-19 announcement